POTENSI TUMBUHAN PAKAN ALAMI bagi MONYET HITAM SULAWESI (Macaca nigra) di HUTAN LINDUNG GUNUNG MASARANG - Rivo F. Rahasia; Johny S. Tasirin; Martina A. Langi; Saroyo Sumarto (COCOS, 2014)
ABSTRACT Mount Masarang Forest Reserve covers an area of 158,48 ha and is part of the natural habitat of the Sulawesi crested black macaque based on the geography and the forest. A population of Sulawesi crested black macaques may thrive here through introduction and migration from nearby populations. This research is aimed to study the potential of natural food plants of the Sulawesi crested black macaque (Macaca nigra) in Mount Masarang Forest Reserve. This research was done from March to April 2013 in Mount Masarang Forest Reserve, Tomohon City. Data was collected using multiple stage random sampling method. From 131 species plants in Mount Masarang Forest Reserve, found 7 species plants naturally eaten by Sulawesi crested black macaques, with varying population densities and role in the community. The species are Alstonia scholaris (5.944 individuals), Piper aduncum (5.225 individuals), Euodia minahassae (3.220 individuals), Trema orientalis (1.486 individuals), Koordersiodendron pinnatum (991 individuals), Caryota mitis (743 individuals) dan Dendrocnide microstigma (495 individuals). The highest distribution of food plants can be found on the eastern slopes, because 42% of the food plants on Mount Masarang Forest Reserve are found on these slopes.Keywords: Macaca nigra, Mount Masarang Forest Reserve, potential of natural food plants